Trends and tree-rings: an investigation of the historical and paleo proxy hydroclimate record of the Khangai Mountain Region of Mongolia - Venable, Niah B. H., author; Fassnacht, Steven R., advisor; Laituri, Melinda J., committee member; Sanford, William E., committee member; Brown, Peter M., committee member (Colorado State University. Libraries, 2016)
The Khangai Mountain region of western central Mongolia is a diverse area of mountain, forest, steppe, and desert steppe landscapes reaching across and beyond the mountains. The tradition of nomadic pastoralism is strong in the region, with water for domestic and livestock needs supplied through lakes, springs, rivers, and wells. Herders of the region have felt impacts from the climatic extremes of the last few decades in terms of increasing temperatures and decreasing water supplies. The main objective of this dissertation is to quantify the changing climate of Mongolia through analysis of key hydrometeorological variables over space and through time. The assessments of trends in the data and the paleo proxy analyses herein address interdisciplinary research questions using multidisciplinary approaches. In closing, this work also examines how the data and analyses presented are used as objects that cross disciplinary boundaries, and can facilitate communication and collaboration between different groups. To provide context for this work, a countrywide view of changing maximum temperature, minimum temperature, and precipitation are examined using trend analyses of gridded datasets. Both minimum and maximum temperatures are significantly warming across the country. Significant decreases in precipitation are concentrated in the central and eastern parts of the country for the 50-year period of analysis. Local knowledge of hydroclimatic change provides another source of climatic information with herders of the Khangai Mountain region observing temperature increases, though the exact time period over which change has occurred varies depending upon memory. Therefore, temperature data were analyzed from five meteorological stations with varying lengths of record from 15 to 50 years and varying start periods based on the available length of record. The most highly significant changes occurred for the longest time periods and for annual average minimum temperatures. Issues of data availability, serial correlation, and homogeneity of climate records were explored using the Mann-Kendall test for trend significance and the Thiel-Sen method for determining trend slope or magnitude in precipitation and streamflow records. An additional step of prewhitening the data prior to testing was used to reduce the influence of autocorrelation on results. Homogeneity testing was also performed. Decreasing trends in annual, spring, and summer precipitation and/or streamflow were found at several Mongolian stations, particularly on the northern side of the mountains, with increasing winter precipitation trends at one site. Results were compared to analyses using Colorado data. Degradation of the Colorado hydroclimate records by shortening the time series and introducing gaps to simulate inconsistencies found in Mongolian datasets created significant trends where none previously existed. Tree-ring reconstructions of Mongolian hydroclimate variables have provided insight on multidecadal and muticentennial trends in climate variability over many other parts of the country, but that work has not been extended to contextualize the recent sharply decreasing streamflows of the Khangai Mountain region. Cores from two new sites collected in the summer of 2012 and records from eight other moisture-sensitive sites in the region were used to reconstruct streamflow for four gages. Missing streamflow data were filled by multiple imputation/predictive mean matching methods with data from six nearby meteorological stations prior to use in multiple linear regression models developed for the reconstructions. A quantitative evaluation of reconstructed and historical extremes of wet and dry conditions in each basin and qualitative analyses of event synchrony are discussed. The drought events of the last decade and a half, while extreme are not beyond the range of natural variability found over the last 300+ years in the four Khangai Mountain region rivers and could be considered plausible flow conditions for the future, particularly under a warming and possibly drying climate. Finally, this dissertation explores cross-boundary connections within each previous chapter and contributions of this work to selected goals of the Mongolian Rangelands and Resilience (MOR2) project, an interdisciplinary and cross-cultural collaboration investigating the resilience of Mongolian pastoral systems to climate change. Changes to the livelihoods of traditional nomadic pastoralists of Mongolia are not only attributable to climate, but also represent changes to socio-ecological, economic, and governmental/policy systems. The analyses of observational gridded, station-based, and paleo proxy data in this dissertation provide a quantitative foundation for continued investigations of the physical hydroclimate systems of the region and further themes developed in previous research from across Asia and within Mongolia. The results of this work will prove useful as a foundation for the development of water policy and infrastructure ideally favoring sustainable nomadic pastoral use of the region’s finite water resources under a changing climate.